2022
DOI: 10.1007/s00405-022-07298-7
|View full text |Cite
|
Sign up to set email alerts
|

Measured and self-reported olfactory function in voluntary Norwegian adults

Abstract: Purpose The lack of epidemiological data on the proportion of olfactory dysfunction (OD) using comprehensive olfactory assessment in healthy adults in Scandinavia motivated to the present study which aimed to explore the proportion of OD in voluntary healthy Norwegian adults, assessed by Sniffin’ Sticks, and its correlation to self-reported olfactory function. Furthermore, sociodemographic and clinical factors associated with olfactory function were analysed. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Our data suggested that the CRI-Education sub-score may have a minor contribution in women, as indicated in a previous study [ 17 ]. Instead, Heian and colleagues showed that men with low education had lower olfactory function scores after a comparison between self-reported tests and Sniffin’ sticks data analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that the CRI-Education sub-score may have a minor contribution in women, as indicated in a previous study [ 17 ]. Instead, Heian and colleagues showed that men with low education had lower olfactory function scores after a comparison between self-reported tests and Sniffin’ sticks data analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%